(untitled) (Research, Society and Development, 2020)
This research attempt to design the information system of village government (SIM PEDES) using the approach of action research as one of useful method can be used as a strategy of Information System using with a purpose to support the effectiveness of Village government managerial system in Wargakerta, Sukarame, Tasikmalaya. The application of Information system havebeen adjusted within the needs of Wargakerta village, therefore it can help the current business process. SIM PEMDES Application Program consist of various feature start from the system of population management, system of employee management, system of land and building tax management, system of village financial management, and the system of village potential management. Beside, this strategy of system information using can be made as the first step guide to develop a village management information system which refers to the development of Digital Village. The result of this research showed how SIM PEMDES Application is quite effective to help the management process of Wargakerta.